Ideological Construction of the Mass Media: Study of Religious Moderation News in the National Online News Media and its Relation to Moderate Da’wah - Sunaryanto, Sunaryanto; Rizal, Sofyan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study analyzes the ideological construction of the mass media in reporting on religious moderation and its relation to moderate da’wah on Kompas.com and Mediaindonesia.com. This research is a type of qualitative research. News as a unit of analysis was selected by purposive sampling each of 3 (news) for each media. Problems are analyzed with Robert M. Entman's framing analysis which is part of the analysis of mass media texts. This research concludes that Kompas and Media Indonesia construct ideology in religious moderation news which is associated with issues of intolerance and radicalism. These two national media construct news on religious moderation using a moderate national ideology. Concerning moderate da’wah, these two national media do not directly write news with moderate da’wah messages. These two national media construct support for moderate da’wah narratives by constructing religious moderation news. Ideologically, these two national online news media construct news by supporting the practice of religious moderation and the practice of moderate da’wah. The implication is that these two national online mass media need to continue to produce news campaigning for religious moderation and moderate da’wah. News construction related to religious moderation and moderate da’wah needs to be done to help prevent the emergence of radical, extremist, and liberal views.